Ergonomické zásady navrhování obráběcích strojů - Doležal, David (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2019)
Tato práce je zaměřena na ergonomické požadavky při navrhování obráběcích strojů. V práci jsou popsány legislativní požadavky EU a ČR vztahující se k ergonomii. Byl proveden systémový rozbor ergonomických zásad. V práci jsou popsány normy obecně a dále vypsány konkrétní normy, které řeší ergonomii.

This Bachelor thesis is focused on ergonomics requirements for machine tools designing. Thesis includes descriptions of legislative descriptions of EU and Czech Republic, which are related to the ergonomics. Analysis of ergonomics requirements was performed like a part of the thesis. The main standards are detailly described in the thesis and also are mentioned other related sources, which are related which ergonomics..
Ergonomic design principles by machine tools
Keywords: Ergonomie; ergonomické zásady; efektivita práce; bezpečnost práce; ergonomické navrhování; Ergonomics; principles of ergonomics; work efficiency; safety at work; ergonomics designing